SOSIALISASI ANTI BULLYING DI SDN JAMBESARI 01 UNTUK PENCEGAHAN KEKERASAN - Rustantono, Hendra; Nafisatulkhoiroh, Nahdziya; Andriyansah, Andriyansah; rahayu, Masri; Tjiptady, Bella Cornelia; Yanti, Yulia Eka; Cholifah, Tety Nur (FIP UNIRA MALANG, 2026)
Bullying in elementary schools is a serious issue that negatively impacts children’s physical, psychological, social, and academic development. This community service program aims to provide anti-bullying socialization to students of SDN Jambesari 01 to increase their understanding of the forms, impacts, and prevention strategies of bullying. The program applied a participatory approach through counseling, interactive discussions, and case simulations. The results showed an increase in students’ knowledge of bullying types, greater empathy for victims, and a collective commitment to creating a safe and comfortable learning environment. Challenges such as students’ limited initial understanding and low parental attention were addressed through communicative strategies and collaboration with teachers. Thus, anti-bullying socialization is effective as a preventive step in reducing violence in elementary schools.